Active Galactic Nuclei and Host Galaxies in COSMOS-Web. II. First Look At the Kiloparsec-scale Dual and Offset AGN Population - Junyao Li; Ming-Yang Zhuang; Yue Shen; Marta Volonteri; Nianyi Chen; Tiziana Di Matteo (The Astrophysical Journal)
Kiloparsec-scale dual and offset active galactic nuclei (AGNs) are signposts of accreting supermassive black holes (SMBHs) triggered during late-stage galaxy mergers, offering crucial insights into the coevolution of SMBHs and galaxies. However, robustly confirmed systems at high redshift (e.g., z > 1) are scarce and biased toward the most luminous and unobscured systems. In this study, we systematically search for kiloparsec-scale (projected separation <15 kpc) dual and offset AGNs around 571 moderate-luminosity, X-ray-selected AGNs, including the obscured population, utilizing deep Hubble Space Telescope Advanced Camera for Surveys/F814W and multiband JWST NIRCam imaging from the COSMOS-Web survey. We identify 59 dual and 30 offset AGN candidates in late-stage major mergers based on spatially resolved spectral energy distribution analyses. This translates to ∼28 and ∼10 bona fide dual and offset AGNs, using a probabilistic pair-counting scheme to minimize chance superpositions. Notably, the fraction of dual and offset AGNs among moderate-luminosity ( L _bol ∼ 10 ^43 −10 ^46 erg s ^−1 ) obscured AGNs is nearly 2 orders of magnitude higher than that of the most luminous, unobscured quasar pairs. We find tentative evidence for an increasing pair fraction among AGNs with redshift (from a few percent at z ∼ 0.5 to $\sim 22.{9}_{-17.7}^{+27.5} % $ at z ∼ 4.5) and a higher occurrence rate of dual over offset AGNs. There is no pileup of dual/offset AGNs below ∼2kpc separations. These results generally align with predictions from the ASTRID and Horizon-AGN cosmological simulations, when matching sample selection criteria, implying a high probability of both black holes being active simultaneously in late-stage major mergers.